67.4k views
1 vote
F = C + 32, for C Select one: A. C = (F - 32) B. C = C. C = (F - 32) D. C =

User Mitra
by
5.6k points

2 Answers

1 vote

Answer:

Option A is correct :

C = F - 32

Explanation:

F = C + 32

We are solving for C.

Let's subtract 32 from both sides:

F - 32 = C + 32 - 32

F - 32 = C + 0

F - 32 = C

We can also rewrite it as:

C = F - 32

C = (F - 32)

Math is fun

User Te Ko
by
5.3k points
3 votes

Answer:

A. C= (F-32)

Explanation:

F = C + 32

make c the subject of formula

F = C + 32

subtract 32 from both sides

F-32 = C + 32-32

F-32 = C

User Laure
by
5.3k points